Acetonic Fraction of Bidens pilosa Enriched for Maturase K Is Able to Control Cerebral Parasite Burden in Mice Experimentally Infected With Toxoplasma gondii - Mota, Caroline Martins; Santiago, Fernanda Maria; Cardoso, Mariana de Resende Damas; Rostkowska, Cristina; de Oliveira, Taísa Carrijo; Silva, Deise Aparecida de Oliveira; Pirovani, Carlos Priminho; Mineo, Tiago Wilson Patriarca; Mineo, José Roberto (Frontiers in Veterinary Science, 2019)
Toxoplasma gondii infection can cause abortions or congenital infection for a vast number of domestic animals and humans, leading to economic loss in veterinary sciences, as well as severe consequences for immunocompromised patients. Bidens pilosa Linné has been used in ethnopharmacology for treatment of diseases, as malaria, diabetes and hepatitis, in addition to its use as antioxidant, antiallergic, anti-inflammatory, and antiviral. The components of this plant have never been studied before for treatment of toxoplasmosis, and the conventional drugs currently used to treat this disease have high degree of toxicity. Thus, the aim of this study was to evaluate the effect of B. pilosa against T. gondii, by analyzing a total extract of this plant in parallel with a fraction obtained by precipitation in acetone. Also, it was assessed if the acetonic fraction could present lectinic activity, followed by its identification by mass spectrometry. It was observed with the experimental models designed that both total extract and acetonic fraction of B. pilosa were able to control T. gondii infection by in vitro and in vivo experiments, in addition to their low toxicity to host cells. Both total extract and acetonic fraction of this plant display capacity to impair replication of T. gondii tachyzoites. Interesting, the B. pilosa acetonic fraction treatment for 10 days after infection decreases significantly the number of T. gondii brain cyst in comparison with controls. The protein isolated from B. pilosa acetonic fraction was characterized as a novel lectin identified as maturase K. Taken together, these findings open new perspectives to treat patients infected by T. gondii. Future studies will be necessary to investigate the precise mechanism underlying the control of T. gondii infection to impair the replication of this parasite in the host cells after treatment with B. pilosa maturase K.